The aqueous alteration of CM chondrites, a review. (15th April 2021) - Suttle, M.D.; King, A.J.; Schofield, P.F.; Bates, H.; Russell, S.S.
Abstract: The CM chondrites are samples of primitive water-rich asteroids formed during the early solar system. They record significant interaction between liquid water and silicate rock, resulting in a mineralogy dominated by hydrated secondary phases. Their similarity to the near-Earth asteroids Bennu and Ryugu – targets of current sample return space missions – makes the analysis of CM chondrites essential to the interpretation of these enigmatic bodies. Here, we review the aqueous alteration history of the CM chondrite group. Initially, amorphous silicate, metal and sulphides within the matrix were converted into Fe-cronstedtite and tochilinite. Later, the serpentinization of refractory coarse-grained inclusions led to the addition of Mg to the fluid phase. This is reflected in the cation composition of secondary phases which evolved from Fe-rich to Mg-rich. Although most CM meteorites are classified as CM2 chondrites and retain some unaltered anhydrous silicates, a few completely altered CM1s exist (∼4.2% [Meteoritical Bulletin, 2021]). The extent of aqueous alteration can be quantified through various techniques, all of which trace the progression of secondary mineralization. Early attempts employed petrographic criteria to assign subtypes – most notably the Browning and Rubin scales have been widely adopted. Alternatively, bulk techniques evaluate alteration either by measuring the ratio of phyllosilicate to anhydrous silicate (this can be with X-ray diffraction [XRD] or infrared spectroscopy [IR]) or by measuring the combined H abundance/δD compositions. The degree of aqueous alteration appears to correlate with petrofabric strength (most likely arising due to shock deformation). This indicates that aqueous alteration may have been driven primarily by impact rather than by radiogenic heating. Alteration extent and bulk O-isotope compositions show a complex relationship. Among CM2 chondrites higher initial water contents correspond to more advanced alteration. However, the CM1s have lighter-than-expected bulk compositions. Although further analyses are needed these findings could suggest either differences in alteration conditions or initial isotopic compositions – the latter scenario implies that the CM1 chondrites formed on a separate asteroid from the CM2 chondrites. Secondary phases (primarily calcite) act as proxies for the conditions of aqueous alteration and demonstrate that alteration was prograde, with an early period at low temperatures (<70 °C), while later alteration operated at higher temperatures of 100–250 °C. Estimates for the initial water-to-rock ratios (W/R) vary between 0.2–0.7. They are based either on isotopic mass balance or mineral stoichiometry calculations – variability reflects uncertainties in the primordial water and protolith compositions and whether alteration was open or closed system. Some CM chondrites (<36%) experienced a later episode of post-hydration thermal metamorphism, enduring peak temperatures <900 °C and resulting in a dehydrated mineralogy and depleted volatile element abundances. Heating was likely short-duration and caused by impact events. The presence of CM chondrite material embedded in other meteorites, their prominence among the micrometeorite flux and the link between CMs and rubble-pile C-type near-Earth asteroids (e.g. Bennu and Ryugu) implies that the CM parent body was disrupted, leaving second-generation CM asteroids to supply material to Earth.